Practice patterns in the administration of late preterm antenatal corticosteroidsAJOG Global Reports at a Glance - Moti Gulersen, MD, MSc; Cynthia Gyamfi-Bannerman, MD, MSc; Michelle Greenman, MD; Erez Lenchner, PhD; Burton Rochelson, MD; Eran Bornstein, MD (Elsevier, 2021)
BACKGROUND: Given the unpredictable nature of preterm birth and the short-term impact of antenatal corticosteroids on neonatal outcomes, optimal timing of antenatal corticosteroid administration (2-7 days from expected birth) remains challenging. OBJECTIVE: We set out to evaluate the likelihood of delivery between 2 and 7 days after antenatal corticosteroid administration in the late preterm period and whether this differs based on the indication for corticosteroid administration. STUDY DESIGN: Retrospective cohort of all singletons that received antenatal corticosteroids in the late preterm period (34 0/7 to 36 6/7 weeks' gestation) and delivered within a large health system between November 2017 and March 2020. Women who received antenatal corticosteroids before the late preterm period, major fetal structural malformations, and cases with missing data were excluded. Cases were stratified on the basis of the indication for antenatal corticosteroid administration, that is, anticipated spontaneous late preterm birth or medically indicated late preterm birth. The primary outcome was delivery between 2 and 7 days after the administration of the first dose of antenatal corticosteroids. Secondary outcomes included time interval from antenatal corticosteroid administration to delivery and delivery during the first 2 days or later than 7 days after antenatal corticosteroid administration. Multivariable logistic regression was performed to evaluate factors associated with optimal timing while adjusting for potential confounders. RESULTS: Of the 1238 patients included in the study, 656 (53%) delivered within the first day after antenatal corticosteroid administration and thus received only the first of 2 doses. Regardless of the indication for late preterm antenatal corticosteroid administration, the likelihood of delivery between 2 and 7 days later was 13.3% (165 of 1238). Moreover, it was more common (23.4% vs 5.0%; P≤.001) (Table 2) and more likely (adjusted odds ratio, 5.88; 95% confidence interval, 4.00-9.09) in women at risk of medically indicated preterm birth than in those with anticipated spontaneous preterm birth. Furthermore, women with anticipated spontaneous preterm birth had a shorter time interval from antenatal corticosteroid administration to delivery (10.7 vs 49.71 hour; P≤.001). CONCLUSION: Regardless of the indication for late preterm antenatal corticosteroid administration, the likelihood of delivery between 2 and 7 days later was low. Nevertheless, our data suggested that delivery within the desired time interval of antenatal corticosteroid administration is more common in women at risk of medically indicated late preterm birth compared with those at risk of spontaneous late preterm birth.